Chemistry - Zumdahl, Steven S. (Houghton Mifflin, 1997)
This is a textbook for college-level general chemistry, not introductory organic chemistry. It provides concise, generally clear explanations of basic chemical concepts. College-level chemistry is a difficult course for many college students today in large part due to their poor preparedness to study at college level.